2006
DOI: 10.5551/jat.13.295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 3-hydroxy-3-methylglutaryl Coenzyme A Reductase Inhibitors on Ubiquinone Levels in Rat Skeletal Muscle and Heart: Relationship to Cytotoxicity and Inhibitory Activity for Cholesterol Synthesis in Human Skeletal Muscle Cells

Abstract: Although statins are prescribed as relatively safe and effective drugs for hypercholesterolemic patients, it has been reported that a significant side effect, myopathy, occurs infrequently during medication. Moreover, because statins decrease cardiac ubiquinone levels, the risk of cardiac dysfunction has been suggested. This study sought to evaluate and compare the cytotoxicity of statins (cerivastatin, pitavastatin, fluvastatin, simvastatin, atorvastatin and pravastatin) in cultured human skeletal muscle cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
1
10
1
1
Order By: Relevance
“…11, 13, 15, 17, 26 These previous data are consistent with our results showing that statins, especially fluvastatin, induced significant inhibition of the viability of lymphoma cells. We next documented that apoptosis was responsible for fluvastatin-induced cytotoxicity towards A20 cells using flow cytometry, HO/PI double staining, TEM, DNA fragmentation and annexin V-FITC staining, indicating that fluvastatin treatment directly induced an apoptotic death in lymphoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…11, 13, 15, 17, 26 These previous data are consistent with our results showing that statins, especially fluvastatin, induced significant inhibition of the viability of lymphoma cells. We next documented that apoptosis was responsible for fluvastatin-induced cytotoxicity towards A20 cells using flow cytometry, HO/PI double staining, TEM, DNA fragmentation and annexin V-FITC staining, indicating that fluvastatin treatment directly induced an apoptotic death in lymphoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…However, the mechanism of statin-induced myopathy is not yet fully understood. Several hypotheses have been proposed to explain statin-induced myotoxicity, including the lowering of ubiquinone levels (5,6), alterations of chloride channel conductance within myocytes (7), and apoptosis induction (8 -10). HMG-CoA reductase, which converts HMG-CoA to mevalonate, is a rate-limiting enzyme of the mevalonate cascade (11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CoQ 10 is involved in mitochondrial electron transport and oxidative phosphorylation [19], but that it cannot suppress statin-induced skeletal muscle toxicity [24]. Therefore, these results suggest that mitochondrial electron transport and oxidative phosphorylation and CoQ 10 are not involved in the acceleration of statin-induced apoptosis and cytotoxicity by uremic toxins on RD cells.…”
Section: Resultsmentioning
confidence: 78%
“…Subsequently, statins decrease activity of small G proteins such as Ras and Rho, which are associated with apoptotic signals [18]. Reduced biosynthesis of coenzymeQ-10 (CoQ 10 ) results in abnormal oxidative phosphorylation in the mitochondrial electron transport chain, which damages cellular homeostasis [19]. Furthermore, interleukin-(IL)-1β- and IL-6-induced oxidative stress promotes hepatic cholesterol synthesis [20].…”
Section: Introductionmentioning
confidence: 99%